High expression of QSOX1 reduces tumorogenesis, and is associated with a better outcome for breast cancer patients - Pernodet, Nicolas (BioMed Central, 2012)
INTRODUCTION: The gene quiescin/sulfhydryl oxidase 1, QSOX1, encodes an enzyme directed to the secretory pathway and excreted into the extracellular space. QSOX1 participates in the folding and stability of proteins and thus could regulate the biological activity of its substrates in the secretory pathway and/or outside the cell. The involvement of QSOX1 in oncogenesis has been studied primarily in terms of its differential expression in systemic studies. QSOX1 is overexpressed in prostate cancers and in pancreatic adenocarcinoma. In contrast, QSOX1 gene expression is repressed in endothelial tumors. In the present study, we investigated the role of QSOX1 in breast cancer. METHODS: We analyzed QSOX1 mRNA expression in a cohort of 217 invasive ductal carcinomas of the breast. Moreover, we investigated QSOX1's potential role in regulating tumor growth and metastasis using cellular models in which we overexpressed or extinguished QSOX1 and xenograft experiments. RESULTS: We showed that the QSOX1 expression level is inversely correlated to the aggressiveness of breast tumors. Our results show that QSOX1 leads to a decrease in cell proliferation, clonogenic capacities and promotes adhesion to the extracellular matrix. QSOX1 also reduces the invasive potential of cells by reducing cell migration and decreases the activity of the matrix metalloproteinase, MMP-2, involved in these mechanisms. Moreover, in vivo experiments show that QSOX1 drastically reduces the tumor development. CONCLUSIONS: Together, these results suggest that QSOX1 could be posited as a new biomarker of good prognosis in breast cancer and demonstrate that QSOX1 inhibits human breast cancer tumorogenesis.